Safety evaluation of whey derived beta-lactoglobulin, Lacprodan® BLG - Dybdahl, Marianne (Toxicol Rep, 2021)
The safety of Lacprodan® BLG, a whey-based protein, was evaluated with respect to genotoxicity and sub-chronic toxicity according to regulatory requirements. Lacprodan® BLG did not show any mutagenic potential in a bacterial reverse mutation assay or any clastogenic or aneugenic potential in an in vitro micronucleus assay performed in human lymphocytes. In a sub-chronic toxicity study, groups of 10 male and 10 female Wistar rats received the test item orally by gavage for 90 days at dose levels of 100, 300 and 1000 mg/kg bw/day. A control group, also including 10 male and 10 female rats, received sterile water, as vehicle. No treatment-related clinical observations or toxicological effects on body or organ weights, food consumption, ophthalmic effects, hematology, clinical chemistry, fertility, urinalysis, or pathology were identified. Therefore, the no-observed-adverse-effect level (NOAEL) for Lacprodan® BLG in the 90-day toxicity study was established as 1000 mg/kg bw/day, corresponding to the highest dose level administered.